2015
DOI: 10.1111/imm.12463
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐155 regulates interferon‐γ production in natural killer cells via Tim‐3 signalling in chronic hepatitis C virus infection

Abstract: SummaryHost immune responses must be tightly regulated by an intricate balance between positive and negative signals while fighting pathogens; persistent pathogens may usurp these regulatory mechanisms to dampen host immunity to facilitate survival in vivo. Here we report that Tim-3, a negative signalling molecule expressed on monocytes and T cells, is up-regulated on natural killer (NK) cells in individuals chronically infected with hepatitis C virus (HCV). Additionally, the transcription factor T-bet was als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(52 citation statements)
references
References 50 publications
4
48
0
Order By: Relevance
“…Some studies have demonstrated that Tim-3 expression is elevated in NKs and that Tim-3 over-expression tends to result from down-regulated miR-155 in NKs during HCV infection, similarly to chronic HBV infection. Blocking Tim-3 can rescue the function of NKs, whereas reconstituting miR-155 can down-regulate Tim-3 [65] . However, a recent study has reported the opposite results.…”
Section: Tim-3 and Nk/nktsmentioning
confidence: 99%
“…Some studies have demonstrated that Tim-3 expression is elevated in NKs and that Tim-3 over-expression tends to result from down-regulated miR-155 in NKs during HCV infection, similarly to chronic HBV infection. Blocking Tim-3 can rescue the function of NKs, whereas reconstituting miR-155 can down-regulate Tim-3 [65] . However, a recent study has reported the opposite results.…”
Section: Tim-3 and Nk/nktsmentioning
confidence: 99%
“…Recently, Tim‐3 was also shown to play important roles in activated T helper 17, cytotoxic T cell 1, macrophages/monocytes, dendritic cells and natural killer cells. A strong correlation between Tim‐3 expression and some chronic diseases has been recently confirmed, such as atherosclerosis and chronic viral infection. Recent data showed that Tim‐3 has a potential relationship with type 2 diabetes.…”
Section: Introductionmentioning
confidence: 97%
“…This is likely to occur by interfering with the TLR7 signaling pathway, upstream of the IFN-a-activated JAK/STAT pathway. The complex balance of immune responses is further illustrated by the finding that, during chronic HCV infections, miR-155 is actually down-regulated in NK cells [30]. This was found to be linked to the up-regulation of Tim-3 and the transcription factor T-bet, with the consequence of a reduction in IFN-g production by these cells.…”
Section: Mir-155 and Hepatitis Virusesmentioning
confidence: 98%